Posidonia oceanica restoration in a threatened Mediterranean Sea - PANSINI, Arianna (Università degli studi di Sassari, 2023)
Seagrass meadows are important coastal ecosystems, providing valuable goods and services contributing to the humankind. In the Mediterranean Sea, Posidonia oceanica is the most iconic endemic seagrass, having a crucial role due to its unique physical, ecological and economical features. In the past decades anthropic impacts combined with the synergic effects of climate change resulted in severe consequences for the maintenance of its integrity, stability, resilience, and productivity. Restoration is considered a strategy to enhance seagrass recovery, even if its outcomes are susceptible to climate change impacts. Decision making for good seagrass restoration in a changing ocean requires valuable information regarding the success of past restorations, finding the knowledge gaps, assessing the capability and resilience of seagrasses to counteract or adapt to future conditions and seagrass responses on restored sites. This thesis aims at testing the reliability and effectiveness of P. oceanica restoration under an expected climate change scenario, developing studies with several approaches. A collated evidence of past restoration actions of P. oceanica was reported by combining a literature systematic review and expert evaluation. Then, several experimental studies aimed at understanding seagrass responses to climate change effects were done: the morphometry and productivity of P. oceanica were evaluated in relation to future warming and extreme climate events, while a similar approach was adopted to understand the seagrass biochemical responses as warming descriptors. Next, a manipulative study investigated the seagrass early development under ocean acidification. The final study aimed at evaluating the resilience of restored P. oceanica to local conditions depending on the opera age. The final chapter is a conclusion that underlies the implication of the whole work, providing insights that lead to efficient restorations of P. oceanica habitat and functioning. Seagrass meadows are important coastal ecosystems, ...